Influence of electric fields and pH on biofilm structure as related to the bioelectric effect. - Stoodley, P (1997)
Mixed species biofilms of Klebsiella pneumoniae, Pseudomonas fluorescens, and Pseudomonas aeruginosa were grown in a flow cell fitted with two platinum wire electrodes. The biofilm growing on the wires reached a thickness of approximately 50 microm after 3 days. When a voltage was applied with oscillating polarity, the biofilm attached to the wire expanded and contracted. The biofilm expanded by approximately 4% when the wire was cathodic but was reduced to 74% of the original thickness when the wire was anodic. The phenomenon was reproduced by alternately flushing the flow cell with media adjusted to pH 3 and pH 10 with no electric current. At pH 10 the biofilm was unaltered, but it became compacted to 69% of the original thickness at pH 3. We explained these phenomena in terms of the molecular interactions between charged acidic groups in the biofilm slime and the bacterial cell walls. Contraction of the biofilm under acidic conditions may be caused by (i) the elimination of electrostatic repulsion from neutralization of negatively charged carboxylate groups through protonation and (ii) subsequent hydrogen bonding between the carboxylic acids and oxygen atoms in the sugars. Electrostatic interactions between negatively charged groups in the biofilm and the charged wire may also be expected to cause biofilm expansion when the wire was cathodic and contraction when the wire was anodic. The consequences of the explanation of the increased susceptibility of biofilm cells to antibiotics in an electric field, the "bioelectric effect," are discussed.